Life and Hope Association: Engaged Buddhist Strategy Transforming Compassion into Social Action - Chhon, Kimpicheth (International Journal of Multidisciplinary in Management and Tourism, 2020)
This article aims to find the strategy transforming compassion into real social action by Buddhist NGO that considered as a new movement of Buddhist social work in Cambodia. The loving-kindness and compassion as wishing and wanting to see other happy will not be just in the form of compassionate mind when it is taken into action. This study will show one upper step of sustainable development concept from compassion when it is applied by socially engaged Buddhist movement. The engaged Buddhist strategy of Life and Hope Association brings the Buddhist concept of compassion into social well-fares and services for the sustainable development of community and human resources. Bringing disadvantaged children and vulnerable women into the better mainstream society by empowering them through education as the tool to lead their lives and it can be long last impacts for individual and society. This work comes from the real field experience with intensive involving in the organization’s social activities for three months in order to see how this Buddhist NGO’s initiative strategy could bring the needs for sustainable development to meet with the sustainable help that provides the long last impacts that mean for active model transforming compassion into real social action.